Rancangan Lansekap Gedung Kuliah E Kampus Institut Teknologi Kalimantan Sebagai Ruang Multi Fungsi - Denny Huldiansyah; Tiara Rukmaya Dewi; Nadia Almira Jordan (JAUR (JOURNAL OF ARCHITECTURE AND URBANISM RESEARCH), 2022)
The presence of open spaces in the spatial order of the campus can encourage students to engage in outdoor activities aimed at improving their quality of life and academic performance. Providing an integrated, open campus space is the key to creating a unique, dynamic, and aesthetic campus. During development, Institut Teknologi Kalimantan (ITK) continues to develop the infrastructure to support all lecture events, one of which is an open space configuration for College Building E. The landscape design process for this college building is in progress. It consists of five steps consisting of (1) problem identification; (2) data collection; (3) data analysis; (4) formulation of concepts; and (5) Design. The landscape design concept of College Building E conceptually applies the principle of multifunctional space as seen in the design of public green open spaces that combine the functions of public and green spaces. The coexistence of public and green spaces creates harmony in the design of educational, recreational, interactive, aesthetic, and dynamic open spaces.